Research Trends in Environmental Education - Sharma, Kavita (INDIAN EDUCATIONAL REVIEW, 2018)
With a global concern on education for sustainable development, during last few decades, different policy documents have highlighted the need to address it through education from time to time. In India, an important milestone in this direction is the judgment of the Honourable Supreme Court in 2003, which made environmental education mandatory at all levels. Following this, various educational bodies at the national and state levels took measures in this direction; be it development of curriculum, resource material, undertaking researches, extension, training or any other activities. This report is a systematic review of the researches conducted during 2000–2016 in India related to environmental education. It includes M.Ed. and doctoral theses, research articles, conference reports and research projects by different institutions and agencies. Divided into six broad themes, namely awareness and attitude of students and teachers, curricular framework and material such as syllabi, textbooks and teaching-learning materials (TLM), teaching-learning process, teacher development including teacher education curriculum and training, policy and systemic issues; each theme explores the trends of research in the area over the last one and a half decade. The research survey also highlights the gaps in studies under each theme and provides suggestions for future research on environmental education.